2008
DOI: 10.1590/s1516-84842008000600007
|View full text |Cite
|
Sign up to set email alerts
|

Freqüência de hemolisinas anti-A e anti-B em doadores de sangue de Itapeva e Ourinhos

Abstract: Uma transfusão de sangue com o tipo ABO incorreto pode resultar na morte do paciente, com reação hemolítica intravascular, seguida de alterações imunológicas e bioquímicas. Considerando a pequena quantidade de estudos sobre as hemolisinas anti-A e anti-B e a importância desses anticorpos na prática transfusional, o objetivo deste trabalho foi verificar a frequência dessas hemolisinas e a associação a fatores como etnia e gênero em doadores de sangue dos bancos de sangue dos municípios de Itapeva e de Ourinhos,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…( 9 ) Acomparison between two cities in São Paulo state showed high titers for both men and women with an increase in levels in recent years. ( 10 ) The authors did not stratify for age and the technique used for titration was not mentioned. Our titration procedure did not include the determination of IgG titer levels, just IgM.…”
Section: Discussionmentioning
confidence: 99%
“…( 9 ) Acomparison between two cities in São Paulo state showed high titers for both men and women with an increase in levels in recent years. ( 10 ) The authors did not stratify for age and the technique used for titration was not mentioned. Our titration procedure did not include the determination of IgG titer levels, just IgM.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies use a cut-off point of 100 to classify a donor as dangerous using the microplate titration technique. 14 , 15 , 16 , 17 , 18 It should be noted that standardization in the reading of agglutination intensities using this technique is more complex compared to the tube technique in respect to the titer definition of the AABB Technical Manual. The titer is given as the highest dilution that produces a macroscopic agglutination of one cross (1+).…”
Section: Discussionmentioning
confidence: 99%
“…Another study involving 4447 samples of O blood group donors found frequencies of 1.2% of donors classified as dangerous universal donors in Itapeva and 5.3% in Ourinhos both in São Paulo, without distinguishing the influence of each hemagglutinin and without assessing IgG antibodies. 18 …”
Section: Discussionmentioning
confidence: 99%